Molecular regulators of alcoholic liver disease: a comprehensive analysis of microRNAs and long non-coding RNAs - Zhang, Lin; Wang, Rongqi; Nan, Yuemin; Kong, Lingbo (Frontiers in Medicine, 2025)
Many biomolecules and signaling pathways are involved in the development of alcoholic liver disease (ALD). The molecular mechanisms of ALD are not fully understood and there is no effective treatment. Numerous studies have demonstrated the critical role of non-coding RNAs, including long non-coding RNAs (lncRNAs) and microRNAs (miRNAs), in ALD. miRNAs play an important regulatory role in the pathogenesis of ALD by controlling critical biological processes such as inflammation, oxidative stress, lipid metabolism, apoptosis and fibrosis. Among them, miR-155, miR-223 and miR-34a play a central role in these processes and influence the pathological process of ALD. In addition, lncRNAs are involved in regulating liver injury and repair by interacting with miRNAs to form a complex regulatory network. These findings help to elucidate the molecular mechanisms of ALD and provide a scientific basis for the development of new diagnostic markers and therapeutic targets. In this article, we review the roles and mechanisms of LncRNAs and miRNAs in ALD and their potential use as diagnostic markers and therapeutic targets.